Development of monitoring tools for critical success factor in managing occupational safety and health for gas contractor companies in Peninsular Malaysia - Ramat, Hamdan (2016)
There is a need to develop Monitoring Tools for Critical Success Factor in Managing Occupational Safety and Health Management System (OSHMS) for Gas Contractor companies in Malaysia. Critical Success Factor (CSF) is defined as the necessary element that needs to be achieved by companies in order to ensure the success of Occupational Safety and Health (OSH) implementation in tandem with the spirit of Occupational Safety and Health Act 514, 1994 with promotes self-regulatory in work place setting. Critical Success Factor imposed by these industries need to be identified in complying with OSHMS element as to avoid Occupational Safety and Health accident in Malaysia. This study aimed to consolidate the data of Occupational Safety and Health Management System (OSHMS) implementation among Gas Contractor companies in Peninsular Malaysia, identify the Critical Success Factor imposed by these industries and development of monitoring tools for Critical Success Factor in managing occupational safety and health. A total of 80 Gas Contractor companies registered with Department of Occupational Safety and Health (DOSH) in Peninsular Malaysia participated to these newly established OSHMS questionnaire and interview check sheet to determine MS 1722:2011 elements conformity and it Critical Success Factor in this cross-sectional study. Descriptive statistic showed main element conformity mean (standard deviation) the highest score is Policy 72(15.5) and the lowest score is Action for Improvement which is 60(20.7). The highest percentage of company that complies with the main element is Policy 15% and the lowest is Organizing 8.8%. The highest partially complied percentage for company element is Policy distributed between 61.0 to 85.0% which is 76.3%. From the Z-score graph, it indicates that the individual company conformity is not much different from each other and based on Z-score analysis it showed the most Critical Success Factor for main element scored among Gas Contractor companies are Organizing and Evaluation 58 companies, followed by Action for improvement 53 companies, Policy 51 companies and lastly Planning and Implementation 49 companies. Result obtained from questionnaire and interview showed that the implementation of OSHMS in Gas Contractor Companies in Peninsular Malaysia is similar between 0.7% - 5% accepts for the Organizing element, which the score was 19.8%. The mean score for almost all of main element is below 70% and the identified Critical Success Factor element for Gas Contractor companies in Peninsular Malaysia is the employer did not allocate responsibility, accountability and authority to Senior Management for effectively implementing and promoting the understanding on OSHMS arrangement to all members of the organization leading to in adequate of Initial Review record and not fully completed continual improvement arrangement. Percentage of conformity with OSHMS MS 1722:2011 elements by Gas Contractor companies can be further improved by focusing on the implementation of developed OSHMS Critical Success Factor Monitoring Tools.